Ethnobotanical study of medicinal plants used by rural inhabitants of the parish San Carlos Quevedo in Ecuador - Zambrano Intriago, Leonardo Fabián; Buenaño Allauca, Mónica Patricia; Mancera Rodríguez, Néstor Javier; Jiménez Romero, Edwin (Universidad y Salud, 2015)
Objective: A study to establish the current state of local knowledge on the use of medicinal plants in the farming communities in rural areas of the parish San Carlos Quevedo, province of Los Rios in Ecuador was performed. Materials and methods: Between February and May 2014 parts of plants used, type of administration, preparation, categories of traditional medicinal use and knowledge by sex and age ranges were established. The species use value (IVU), the relative knowledge of the species by several informants (RVU) and the level of significant use Tramil (UST) was determined. Results: It was found that 43 species of plants had medicinal use, the leaves were the structures most commonly used (76.7%), the primary form of preparation was the infusion (83.7%), and the route of administration employed was the drink (86 %). The best represented medicinal use category is related to the gastrointestinal system (44.2%). No significant differences in the knowledge of species according to sex and age range of the respondents were found. Conclusions: The most important medicinal plants for locals were the lemongrass (Cymbopogon citratus), oregano (Origanum vulgare) and peppermint (Mentha sativa).